GA based Optimal Power Flow Solutions - Garg, Madhu (My University, 2008)
The optimal power flow (OPF) is a non-linear programming and highly constrained optimization problem. The objective is to present solution of optimal power flow problem of large transmission systems via a simple genetic algorithm. The main objective is to minimize the fuel cost and keep the power outputs of generators; bus voltages, shunt capacitors/reactors and transformers tap setting in their secure limits The OPF has been usually considered as the minimization of an objective function representing the generation cost and/or the transmission loss. Even though, excellent advancements have been made in classical methods, they suffer from disadvantages because of the extremely limited capability to solve real-world large-scale power system problems. They are weak in handling qualitative constraints. The major advantage of the GA is that it is relatively versatile for handling various qualitative constraints. It can find multiple optimal solutions in single simulation run. So they are quite suitable in solving multi-objective optimization problems. OPF with reactive power compensation is also investigated in this work. The compensating device investigated in this study is shunt capacitor. Shunt capacitor is installed to provide capacitive reactive compensation/ power factor correction. Shunt capacitors are used to improve the quality of the electrical supply and the efficient operation of the power system. Also flat voltage profile on the system can significantly reduce line losses. Shunt capacitor are relatively inexpensive and can be easily installed anywhere on the network between any of the bus and the ground. The IEEE 30-bus system is investigated in this work.
Keywords: Reactive power compensation, OPF, GA